2017
DOI: 10.1016/j.ttbdis.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the sialome of Hyalomma excavatum

Abstract: Tick saliva contains hundreds or thousands of proteins that help blood feeding by impairing their hosts’ hemostasis, inflammation and immunity. Salivary gland transcriptomes allow the disclosure of this pharmacologically active potion that consists of several multi-gene families, many of which are tick-specific. We here report the “de novo” assembly of ~ 138 million reads deriving from a cDNA library from salivary glands of adult male and female Hyalomma excavatum leading to the public deposition of 5,337 codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 39 publications
(46 reference statements)
3
40
1
Order By: Relevance
“…Thus, knowledge about the vital molecular constituents of ticks, such as genes and/or proteins, have become the target of several studies (CASTRO et al, 2016;CHMELAŘ et al, 2016;DÍAZ-MARTÍN et al, 2015;HEEKIN et al, 2013;KOTSYFAKIS et al, 2015;PERNER et al, 2016;RIBEIRO et al, 2017;XU et al, 2016). These studies have sought to ascertain and understand the roles of the molecules involved in the tick-host or tick-pathogen relationship.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, knowledge about the vital molecular constituents of ticks, such as genes and/or proteins, have become the target of several studies (CASTRO et al, 2016;CHMELAŘ et al, 2016;DÍAZ-MARTÍN et al, 2015;HEEKIN et al, 2013;KOTSYFAKIS et al, 2015;PERNER et al, 2016;RIBEIRO et al, 2017;XU et al, 2016). These studies have sought to ascertain and understand the roles of the molecules involved in the tick-host or tick-pathogen relationship.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have sought to ascertain and understand the roles of the molecules involved in the tick-host or tick-pathogen relationship. In addition, there is great interest in discovering new molecules with potential for use within biotechnology and pharmacology, which might help in developing new control methods (CHMELAŘ et al, 2016;DÍAZ-MARTÍN et al, 2015;RIBEIRO et al, 2017). The evolutionary context of bloodsucking organisms is another prominent approach that has been studied, through making inferences about the evolution of genes and proteins, thereby helping to improve knowledge about the hematophagic behavior of the arthropods (MANS et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Custom bioinformatic analysis were describe elsewhere (Karim, Singh, & Ribeiro, ; Ribeiro, Slovak, & Francischetti, ) with modifications. Low‐quality reads were trimmed from Fastq files (less than 20) and contaminating adapter primer sequences were removed.…”
Section: Methodsmentioning
confidence: 99%
“…They found significant change in the banding pattern of salivary gland proteins of ticks incubated at various temperatures. In a study conducted by Ribeiro et al (2017), it has been observed that mucins, glycine-rich proteins, anticoagulants of the madanin family, metalloproteases and lipocalins are the proteins among the most secreted by H. excavatum.…”
Section: Significance Of Salivary Glands Of Hyalommamentioning
confidence: 99%